Developing a Process Drama-Based Instructional Model to Enhance English-Speaking Ability of English for Specific Purposes (ESP) Students in Chinese Vocational Colleges - Peng, Cheng; Wanpen, Supatra; Jansrisukot, Julamas (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: 1) study the current problems in the English-speaking ability, and 2) develop and validate an instructional model based on social constructivist theory, collaborative learning, and process drama. Participants included 240 second-year tourism management students and 6 English teachers selected through purposive sampling to identify core pedagogical gaps. Additionally, five experts in curriculum and instruction validated the model. Data were collected via structured questionnaires and semi-structured interviews. The validation of the research instruments was confirmed using the Index of Item-Objective Congruence (IOC), while the model's suitability was assessed using a 5-point Likert scale (1=Lowest, 5=Highest). Results indicated that students face significant linguistic barriers and affective factors like high anxiety. The developed model, titled the SCPD Model, consists of three stages (Pre-activity, While-activity, and Post-activity) and nine instructional steps. Expert validation yielded a high mean score of 4.31 (SD = 0.52). The research provides a validated framework for enhancing oral communication in vocational ESP contexts.